RECONSTRUCTING “NASIONALISME” WITHIN QUR’ANIC EXEGESIS: A CRITICAL DISCOURSE ANALYSIS OF AHMAD HASSAN’S TAFSIR AL-FURQAN - M. Khai Hanif Yuli Edi Z; Muhajirin; Lukman Nul Hakim; Syefriyeni (Peminat Ilmu Ushuluddin, 2025)
This study examines Ahmad Hassan’s interpretation of ‘Nasionalisme’ in Tafsir Al-Furqan by employing Norman Fairclough’s Critical Discourse Analysis (CDA). It aims to analyze how discourses of ‘nasionalisme’—particularly those concerning love for the homeland and obedience to political authority—are constructed, negotiated, and legitimized within a Qur’anic exegetical framework. Using qualitative library research, the primary sources consist of Tafsir Al-Furqan and Ahmad Hassan’s Islam dan Kebangsaan, while secondary sources include scholarly books, academic journals, and other relevant works. In terms of methodology, this study applies Fairclough’s three-dimensional model of CDA, encompassing textual analysis, discursive practice, and sociocultural practice. The findings demonstrate that Ahmad Hassan constructs a form of religiously grounded “Nasionalisme” through conditional theological framing. Love for the homeland is articulated as a legitimate Islamic value insofar as it remains consistent with tawḥīd and sharī‘ah, while obedience to political leaders if it aligns with Islamic law. From a discursive perspective, Ahmad Hassan’s interpretation functions as an alternative to the dominant secular nationalist discourse that appear during the presidency of Soekarno. His exegetical strategy reveals an effort to reconstruct ‘nasionalisme’ not as an absolute political loyalty, but as a moral and religious commitment oriented toward justice, social responsibility, and resistance to ideological domination. By positioning ‘nasionalisme’ within Islamic normative boundaries and Indonesia’s socio-political context, this study contributes to the broader discourse on Qur’anic exegesis and the dynamic relationship between Islam, ‘nasionalisme’, and the nation-state in Indonesia.